Wi-Fi Indoor Navigation System Controlled Automated Wheelchair - Lim, Alyssa Raphaella G.; Rabacca, Jan Carlo D.; Valdez, Esteen; Sybingco, Edwin; Sapang, Oswald; Roque, Maria Antonette; Gustilo, Reggie (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Wi-Fi Indoor Navigation System Controlled Automated Wheelchair aims to give a motorized wheelchair the capability to self-navigate in an indoor environment. With the use of two (2) cameras attached on the sides of the wheelchair, the wheelchair will be able to know its current location by scanning the QR codes attached to an adjacent wall. The wheelchair can enable a person to go to the desired location through the controller or make a manual maneuvering with the use of joystick. The wheelchair performs obstacle detection and avoidance using ultrasonic sensors, manual control whilst capable of autonomous operation.